2016
DOI: 10.1073/pnas.1600537113
|View full text |Cite
|
Sign up to set email alerts
|

Pathological ribonuclease H1 causes R-loop depletion and aberrant DNA segregation in mitochondria

Abstract: The genetic information in mammalian mitochondrial DNA is densely packed; there are no introns and only one sizeable noncoding, or control, region containing key cis-elements for its replication and expression. Many molecules of mitochondrial DNA bear a third strand of DNA, known as "7S DNA," which forms a displacement (D-) loop in the control region. Here we show that many other molecules contain RNA as a third strand. The RNA of these R-loops maps to the control region of the mitochondrial DNA and is complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 47 publications
2
71
0
Order By: Relevance
“…A growing number of mitochondrial disorders are now understood to feature mtDNA aggregation or clustering (Almalki et al , ; Akman et al , ; Desai et al , ; Nicholls et al , and this report). Clustering of the different complexes appears to be remarkably well tolerated, in that OXPHOS subunits continue to be produced and assembled correctly in the vicinity of the mtDNA aggregates, as respiratory capacity can remain at normal levels ().…”
Section: Discussionmentioning
confidence: 78%
“…A growing number of mitochondrial disorders are now understood to feature mtDNA aggregation or clustering (Almalki et al , ; Akman et al , ; Desai et al , ; Nicholls et al , and this report). Clustering of the different complexes appears to be remarkably well tolerated, in that OXPHOS subunits continue to be produced and assembled correctly in the vicinity of the mtDNA aggregates, as respiratory capacity can remain at normal levels ().…”
Section: Discussionmentioning
confidence: 78%
“…Increased R-loop formation in RNase H-deficient yeast strains subjected to Top1 inhibition led to origin-independent DNA replication initiation in the rDNA [28]. Finally, the mitochondrial genome is thought to initiate DNA replication priming through R-loop intermediates [70][71][72] and a recent study showed that replication origins are specified in an R-loop dependent manner at murine class switch immunoglobulin regions [73].…”
Section: Discussionmentioning
confidence: 99%
“…However, D-loop functionality also depends on factors encoded by the nucleus, including RNASEH1 (ref. 49), which might affect the risk of reversion. Another suggestion is that perinuclear mitochondria are somehow preferentially replicated 50 .…”
Section: Challenges and Solutionsmentioning
confidence: 99%